Perspectives and evaluation on the effect of financial burden relief of medical insurance for people with catastrophic diseases and its influencing factors - Guo, Pengfei; Qin, Yinghua; Wang, Rizhen; Li, Jiacheng; Liu, Jingjing; Wang, Kexin; Li, Ye; Kang, Zheng; Hao, Yanhua; Liu, Huan; Sun, Hong; Cui, Yu; et al. (Frontiers in Public Health, 2023)
Background: Catastrophic disease sufferers face a heavy financial burden and are more likely to fall victim to the “illness-poverty-illness” cycle. Deeper reform of the medical insurance system is urgently required to alleviate the financial burden of individuals with catastrophic diseases. Methods: Data were obtained from a cross-sectional questionnaire survey conducted in Heilongjiang in 2021, and logistic regression and restricted cubic spline model was used to predict the core factors related to medical insurance that alleviate the financial burden of people with catastrophic diseases. Results: Overall, 997(50.92%) medical insurance-related professionals negatively viewed financial burden relief for people with catastrophic diseases. Factors influencing its effectiveness in relieving the financial burden were: whether or not effective control of omissions from medical insurance coverage (OR=4.04), fund supervision (OR=2.47) and degree of participation of stakeholders (OR=1.91). Besides, the reimbursement standards and the regional and population benefit package gap also played a role. The likelihood of financial burden relief increased by 21 percentage points for each unit increase in the level of stakeholder discourse power in reform. Conclusions: China's current medical insurance policies haven’t yet fully addressed the needs of vulnerable populations, especially the need to reduce their financial burden continuously. Future reform should focus on addressing core issues by reducing the uninsured, enhancing the width and depth of medical insurance coverage, improving the level and capacity of medical insurance governance that provides more discourse power for the vulnerable population, and building a more responsive and participatory medical insurance governance system.